IDENTIFIKASI JENIS-JENIS DAN KARAKTERISTIK MORFOMETRIK KELELAWAR DI GUA FATUBAUN DESA MANUFUI KECAMATAN SANTIAN KABUPATEN TIMOR TENGAH SELATAN - Willem Amu Blegur; Arnold Ch Hendrik; Novi Ivonine Bulu; Anastasia Elu; Yumiarti Manek (Fakultas Pertanian, Universitas Timor, 2020)
Bats are mammals (lactating animals) in flyng, the bats sleep during the day and engage in nocturnal activities, so bats are nocturnal (Suyanto, 2001). The study aims to identify the bats in the caves of Fatubaun village Manufui west Timor housing district based. The study was carried out in July 2019 in the Manufui sub-district Santian district of south central Timor. The method used in this study is that of surveying with sample retrieval techniques is done by using fog nets. The data analysis is done qualitative descriptive. According to research carried out in the Fatubaun cave we have two types of bats Pteropus vampyrus Linn and Microglossus sobrinus, both varieties belong to I order of the Chiroptera and 1 family of the Pteropodidae family.